Preparation of hydrophobic MFI zeolites containing hierarchical micro-mesopores using seeds functionalized with octyltriethoxysilane - Novak, Sara [UNESP]; Chaves, Thiago Faheina [UNESP]; Martins, Leandro [UNESP]; Santilli, Celso Valentim [UNESP] (Elsevier, 2020)
In this work, we report the synthesis of hydrophobic MFI zeolites presenting a mesopore size distribution and high specific external area (∼288 m2 g−1), employing surface functionalization with octyltriethoxysilane (OTEOS). Previously, the MFI seeds were generated from a clear solution, followed by grafting with OTEOS and crystallization by hydrothermal treatment. The modifications of the properties of MFI synthesized with different amounts of OTEOS (0–15 mol%) were confirmed by X-ray powder diffraction, thermogravimetric, and elemental analyses. Contact angle (θ ∼140°) and 29Si NMR (T3 signals) measurements demonstrated that OTEOS was effectively grafted on the zeolite surface, resulting in powders with hydrophobic profiles. The grafting, which was mostly on the external surface, was crucial for avoiding the aggregation of MFI crystals during the synthesis, since the OTEOS chains (C8) caused steric hindrance, while allowing fine-tuning of the intercrystalline mesopore volume and increasing the external surface area. This effect was less pronounced when grafting of the MFI zeolites was carried out using organosilanes with longer carbon chain lengths (C12 and C16). This method enables the easy preparation of functionalized zeolitic materials, where the hierarchical pores and hydrophobic surface are essential characteristics for advanced technological applications.
Keywords: Functionalized zeolite; Hierarchical porosity; Hydrophobic powder; Organosilane